The way of the monk in Tales about Old Matters - M. S. Kolyada (Шаги)
There are many tales in Kojidan (Tales about Old Matters), a setsuwa (short didactic tales) collection compiled in the early 13th century by the nobleman Minamoto-no Akikane, which deal with Buddhist monks. Amongst those monks one can find a multitude of well-known names: there are the founders of the major Japanese schools of Buddhism, such as Kūkai and Saichō, famous miracle-workers (including rainmakers), saints, as well as common monks. The biggest section of Akikane’s collection, consisting of 108 tales, is devoted to monks, but characters who took the vows also appear in other parts of Kojidan. To demonstrate what is the way of the monk, Akikane put together stories about the personal virtues of various characters, as well as tales about a variety of miracles. The ability of working miracles acts as some kind of measure of efficiency on the Way, but it can’t guarantee that a man will not fall from this path if he still is attached to worldly passions and still has bad affections. The author may talk about great saints and builders of temples, but he also includes tales about sinful and cruel monks. As in other collections of setsuwa tales, a picture of the cosmos is constructed, where a miracle is something natural and normal, something that takes place in accordance with the laws of causes and consequences, and due to the response of a buddha or kami to prayer and ritual.